Review article: role of oxidative stress in the progression of non‐alcoholic steatosis - ALBANO, E.; MOTTARAN, E.; OCCHINO, G.; REALE, E.; VIDALI, M. (Alimentary pharmacology & therapeutics, 2005)
Summary The mechanisms responsible for the progression of nonalcoholic fatty liver disease (NAFLD) to more severe liver injury are still poorly understood. Data from animal models suggest that oxidative stress contributes to steatohepatitis and an increase of lipid peroxidation has been documented in human NAFLD. By measuring the titers of circulating antibodies against lipid peroxidation products as markers of oxidative stress we have observed that NAFLD patients have titers of these antibodies significantly higher than in controls. Moreover, the titers of lipid peroxidation‐related antibodies are associated with a 3‐fold increase in the risk of developing advanced fibrosis/cirrhosis. Although the mechanisms causing oxidative stress in NAFLD have not been elucidated, these results support the involvement of lipid peroxidation in the processes leading to liver fibrosis associated with NAFLD.